1983
DOI: 10.1017/s0033291700051539
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of characteristics in the families of patients with anorexia nervosa and normal controls

Abstract: SynopsisThe present study compared families of patients with anorexia nervosa with families of non-anorexic adolescent daughters of a similar social class. All anorexics and adolescent comparison girls and their parents were studied using a variety of psychometric measures. Body size estimation and physical anhedonia were also measured. Family characteristics were assessed using the Family Assessment Measure (FAM). Contrary to the hypotheses, no abnormalities were found in terms of parental attitudes to weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 31 publications
3
49
0
Order By: Relevance
“…Similar observations have been made by Casper (1981), Garfinkel et al (1983), and Heron and Leheup (1984) in uncontrolled evaluations and by Garner et al (1985) and North, Gowers, and Byram (1995) in controlled studies. The familial harmony and expressed satisfaction with family relationships among this group led these authors to speculate that the patients' and the parents' views were influenced by denial and a wish to avoid conflict.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar observations have been made by Casper (1981), Garfinkel et al (1983), and Heron and Leheup (1984) in uncontrolled evaluations and by Garner et al (1985) and North, Gowers, and Byram (1995) in controlled studies. The familial harmony and expressed satisfaction with family relationships among this group led these authors to speculate that the patients' and the parents' views were influenced by denial and a wish to avoid conflict.…”
Section: Discussionsupporting
confidence: 87%
“…Parents of patients with restricting AN indicate less conflict, more cohesivenes, and better relationships with their daughters than parents of bulimic AN patients (Strober, Salkin, Burroughs, & Morrell, 1982). Controlled investigations confirmed that families of bulimic AN patients not only reported more discord than normal families, but also more problems than families of restricting AN patients (Garner, Garfinkel, & O'Shaughnessy, 1985;Garfinkel et al, 1983;Humphrey, 1987).…”
Section: Introductionmentioning
confidence: 97%
“…However, many of the interactions observed in the families of children with IDDM are constructive (52) and, at least early in the illness, may be associated with better metabolic control (53). Disturbances in family dynamics have been observed in families of patients with eating disorders (54,55). However, evidence is insufficient to indicate whether altered family dynamics in IDDM increase the risk for development of an eating disorder.…”
Section: Altered Family Dynamicsmentioning
confidence: 99%
“…Several retrospective and/or uncontrolled studies have suggested that psychological disturbance of varying intensity is present in at least some parents of anorexics (Beumont, Abraham, Argall, George, & Glaun, 1978;Kalucy, Crisp, & Harding, 1977) and that it often antedates the onset of the child's symptoms (Crisp, Hsu, Harding, & Hartshorn, 1980;Morgan & Russell, 1975). On the other hand, a study by Garfinkel et al (1983) failed to show significant differences between parents of anorexics and parents of normal control subjects on various measures of depression and personality functioning. Several recent studies have used self-report indices to compare perceived family relationships among anorexic or bulimic family members with those of normal control subjects.…”
Section: Descriptive Studiesmentioning
confidence: 99%